2017
DOI: 10.3233/thc-171337
|View full text |Cite
|
Sign up to set email alerts
|

Cellular neural network modelling of soft tissue dynamics for surgical simulation

Abstract: Abstract. BACKGROUND: Currently, the mechanical dynamics of soft tissue deformation is achieved by numerical time integrations such as the explicit or implicit integration; however, the explicit integration is stable only under a small time step, whereas the implicit integration is computationally expensive in spite of the accommodation of a large time step. OBJECTIVE: This paper presents a cellular neural network method for stable simulation of soft tissue deformation dynamics. METHOD: The non-rigid motion eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The hardware acceleration of cellular neural networks using FPGAs is actually the parallel signal processing capabilities of FPGAs and the parallelization of algorithms. Cellular networks are a special type of convolutional neural network [24][25]. There is no data correlation between different convolutional operations in the same layer of a convolutional neural network.…”
Section: B Feasibility Analysis Of Parallel Implementation Of Cellulmentioning
confidence: 99%
“…The hardware acceleration of cellular neural networks using FPGAs is actually the parallel signal processing capabilities of FPGAs and the parallelization of algorithms. Cellular networks are a special type of convolutional neural network [24][25]. There is no data correlation between different convolutional operations in the same layer of a convolutional neural network.…”
Section: B Feasibility Analysis Of Parallel Implementation Of Cellulmentioning
confidence: 99%
“…The critical time step decreases as the mesh becomes finer for the blood vessels, increasing the number of simulation steps that prolongs the total computation time; therefore, a careful selection of the included blood vessels and other fine details of the liver needs to be considered for achieving a balance of critical time steps for efficient simulation. For numerical stability, it was reported that neural networks [60,61], adaptive semi-explicit/explicit time marching [59] and unconditionally stable explicit scheme [62] could achieve stable numerical analysis for non-linear dynamic systems; these methods may be incorporated into the proposed method for stable dynamic bio-heat transfer analysis under soft tissue deformation.…”
Section: Discussionmentioning
confidence: 99%
“…Some newly developed numerical methods such as the 3D alpha FEM [12] and edge-based smoothed FEM [13] are focused more on the numerical accuracy, convergence, and stability rather than the real-time computational performance, the proposed algorithm may be incorporated into these methods to enable real-time Pennes bio-heat transfer simulation. In terms of numerical stability, it was reported that neural networks [53,54] can achieve stable simulation in the dynamic mechanical systems; they may be incorporated into the proposed method for stable dynamic bio-heat transfer.…”
Section: Discussionmentioning
confidence: 99%